2016
DOI: 10.4103/0366-6999.183425
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Equity Evaluation for Health Expenditure Among Patients with Rare Diseases in China

Abstract: Background:China has not established social security system for rare diseases. Rare diseases could easily impoverish patients and their families. Little research has studied the equity and accessibility of health services for patients with rare diseases in China. This study aimed to explore the factors that influence health expenditure of rare diseases and evaluate its equity.Methods:Questionnaire survey about living conditions and cost burden of patients with rare diseases was conducted. Individual and family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…diseases face higher costs than others. 16 Also the issue of equity in financing healthcare systems is important in LMICs. Nevertheless, a limited number of Asian countries, including Thailand and Malaysia, have been successful in establishing equity within their systems.…”
Section: Introductionmentioning
confidence: 99%
“…diseases face higher costs than others. 16 Also the issue of equity in financing healthcare systems is important in LMICs. Nevertheless, a limited number of Asian countries, including Thailand and Malaysia, have been successful in establishing equity within their systems.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of age on OOP expenses has been addressed in other studies [34], but this study found that the effect was more pronounced for inpatients with MG. This could be related to the fact that different types of BMI cover the population according to different ages and that they have different reimbursement policies for hospitalization expenses.…”
Section: Discussionmentioning
confidence: 67%
“…Studies often identified study participants (adult and children) from patients receiving outpatient care or through disease centres, patients' associations (19,34,39,43) and national registries (16). Self-administered surveys were used by the BURQOL-RD project, as well as two out of three studies conducted in China (14,28). Of the many studies administering questionnaires, some relied solely on web-based surveys (8,19,27), questionnaires sent by mail (26,29,35), the combination of the two (16,17,(20)(21)(22)(23)25,(29)(30)(31)34,35,45,46) or face to face (28,43) administration.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Rare diseases in general were examined in five cases (14,(33)(34)(35)(36) with three studies focusing on more than one rare disease (15,16,27). Further, three studies included or focused on Duchenne Muscular Dystrophy (15)(16)(17), two on Haemophilia (18,19,47,47) and two on Juvenile Idiopathic Arthritis (20,25) with several other rare diseases addressed just once in the remaining studies.…”
Section: Diseases and Body Systemsmentioning
confidence: 99%